Kinetic and isotherm studies of basic red dye adsorption by axonopus compressus - Raymond, Lim Hung Tat (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
The utilization of Axonopus compressus is introduced as a new absorbent for the removal of cationic dye, BR 46 from the aqueous solution. Various parameters, including pH (3-11), initial solution concentration (50-250 mg L-1), temperature (30- 60 C), adsorbent dosage (0.2-1.00 g), were used to study the effects on BR 46 biosorption. The results appeared that the adsorption process took place well in alkaline condition with optimum pH 9. The adsorption rate decreased when the temperature increases showing the adsorption process is exothermic. The adsorption is favour with increase in adsorbent dosage and initial dye concentration. However the percentage of removal decreased once the amount of dosage reaches more than 0.6 g. The equilibrium data fitted better in Freundlich model, although it also can fit into Langmuir model demonstrate that the adsorption occurs at heterogeneous sites and multilayer biosorption.The maximum monolayer biosorption capacity was 78.74 mg/g with the degree of adsorption 2.17 mg/g. The adsorption process followed the pseudo-second order kinetic model showing chemisorption was involved during adsorption process. Intra-particle diffusion model was used to test the mechanism of rate-determining factor. The results showed that intra-particle diffusion was not the only rate-determining step during adsorption.